An intense luminescent Dy(iii) single-ion magnet with the acylpyrazolonate ligand showing two slow magnetic relaxation processes. (25th September 2018) - Li, Xi-Li; Li, Junfeng; Zhu, Cancan; Han, Bing; Liu, Yingfan; Yin, Zhigang; Li, Fengcai; Liu, Cai-Ming
Abstract : A new Dy(iii )-acylpyrazolonate complex displays both intense yellow-light emission and single-ion magnet behavior with two slow magnetic relaxation processes, acting as a potential bifunctional material. Abstract : A new Dy(iii ) complex formulated as [Dy(pmap)3 (H2 O)2 ]·0.375CH3 COOC2 H5 (1 ) (pmap − = 1-phenyl-3-methyl-4-acetyl-5-pyrazolonate) has been synthesized and characterized. Single crystal X-ray analysis revealed that1 crystallizes in the triclinic space group P 1̄ with two crystallographically independent mononuclear molecules (denoted as Dy1 and Dy2 moieties, respectively) in its unit cell. The investigation of photophysical properties showed that1 displays intense yellow-light emission of Dy(iii ) ions with a notable lifetime value of 12.75 μs. Magnetic measurement demonstrated that1 exhibits single ion magnet (SIM) behavior with two slow magnetic relaxation processes under a 2 kOe direct-current (dc) field. Two distinct slow magnetic relaxation processes can be attributed to the presence of two Dy(iii ) centers with different coordination geometries (square antiprism for Dy1 and triangular dodecahedron for Dy2). Moreover, the assignment of two relaxation processes to Dy1 and Dy2, respectively, was elucidated. All these features suggest that1 is a potential bifunctional material combining luminescent and SIM properties within one molecule. Moreover, 1 represents the first SIM with an intense luminescent property based on the acylpyrazolonate ligand.